2021
DOI: 10.1002/nop2.883
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated nursing care as perceived by nursing students: Findings from a qualitative study

Abstract: During their clinical rotations, nursing students are exposed to real situations, and, alongside good examples of clinical practice, they might also witness examples of poor practice that may threaten patient safety (Ion et al., 2015). Among several experienced nursing practices, missed nursing care (MNC), or any aspect of required nursing care that is omitted (in part or in whole) or delayed (Kalisch, 2006) -also known as care left undone, rationing of nursing care and unfinished nursing care (Bassi et al., 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Team-and unit-based efforts, like hourly rounding interventions have been found effective ways to anticipate and care for patients. [30][31][32][33] Our results suggest that nurses value self-preservation to have a fresh start and a fresh mind to face the next shift. George et al 34 found that professionals working during the COVID-19 pandemic (including nurses) resorted to hobbies and spending time with family as self-preservation strategies.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Team-and unit-based efforts, like hourly rounding interventions have been found effective ways to anticipate and care for patients. [30][31][32][33] Our results suggest that nurses value self-preservation to have a fresh start and a fresh mind to face the next shift. George et al 34 found that professionals working during the COVID-19 pandemic (including nurses) resorted to hobbies and spending time with family as self-preservation strategies.…”
Section: Discussionmentioning
confidence: 70%
“…Anticipated nursing care has been used to prevent missed or delayed care and for time management. [29][30][31] Exemplar nurses utilize anticipation of both nursing care and patient needs to avoid distractions and provide PCC. Anticipation also requires teamwork and proper delegation of tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation